A cloud-based distributed platform for secured EPUB EBOOK contents - Faniband, Yunus Parvej; Ishak, Iskandar; Sidi, Fatimah; Jabar, Marzanah A. (World Academy of Research in Science and Engineering, 2020)
Digital content creators who also own their digitally created content Utilizing Digital Rights Management or DRM in order to safeguard and govern the distribution and usage of their digital contents. The features of digital content protection (such as ebook) ranges from content limitation or transfer, and reading permission to authorized reading hardware or Software, to corporate delivery policies involving identification of users and devices for a definite period. Until today, standard for EPUB does not provide a specific DRM standard to protect eBook copyrights. In this paper, we propose a cloud-based EPUB content protection and control platform and describe the proposed ways in protecting EPUB contents through a cloud-based solution for digital content protection and access regulation. We have implemented a prototype with OpenStack open source cloud computing platform enforce access control and efficient in data management with data-at-rest encryption.